Characterization of FriendFeed — A Web-based Social Aggregation Service - Gupta, Trinabh; Garg, Sanchit; Mahanti, Anirban; Carlsson, Niklas; Arlitt, Martin (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
Many Web users have accounts with multiple different social networking services. This scenario has prompted development of "social aggregation" services such as FriendFeed that aggregate the information available through various services. Using five weeks of activity of more than 100,000 FriendFeed users, we consider questions such as what types of services users aggregate content from, the relative popularity of services, who follows the aggregated content feeds, and why.